New reading experiences for Popular unity: Guillermo Atías’ “tabloid novel” … Y corría el billete - Hochberg, Elizabeth L. (Revista Chilena de Literatura, 2020)
This article examines Guillermo Atías’ self-proclaimed “tabloid novel”… Y corría el billete (1972), which was published during Salvador Allende’s Popular Unity government through the new state publishing house Quimantú. I argue that Atías presents his work as an example of how print media may move beyond traditional journalistic and literary frameworks within a revolutionary context. …Y corría el billete may in this sense be considered to enter into dialogue with Quimantú regarding the importance of creating multilayered educational materials that are able to cater to –and politically influence– a diverse readership with different levels of commitment to Chile’s “road to socialism”.